Extraction, Isolation, Characterization and Antioxidant Potential of Pure Compounds from Adonsonia digitata Leaf Extract - Umaru, Hauwa A.; Umaru, Isaac John; Ahmed, Fasihuddin Badruddin (African Journal of Biochemistry and Molecular Biology Research, 2024)
Introduction: Adonsonia digitata L. (Malvaceae) commonly known as Baobab is a medicinal and nutritional plant. The plant parts are used to treat various ailments such as diarrhoea, malaria and microbial infections. It is reported that it is an excellent antioxidant due to its vitamin C content. Baobab has numerous biological properties including antimicrobial, antiviral, anti-oxidant and anti-inflammatory activities amongst others. Objective: The study involves extraction, Isolation, Characterisation of phytochemicals and eval_uation of antioxidant potential of the pure compounds. Methods: The dried leaf powder was subjected to rotary evaporator to obtain crude extract which was subjected to isolation using chromatography analysis and elucidation using NMR and FTIR. Antioxidant (IC50) potential was determined using 2,2-diphenyl-1- picryl-hydrazyl-hydrate (DPPH). Result: Phytochemical investigation of the Baobab leaf extract through isolation and characterization of a bioactive compound was observed. The leaf extract yielded three compounds characterised as D-Limonene, Thunbergol and (z)-2-Methyl-7-octadecene. Conclusion: The analysis of the chemical component reported identified compounds from Baobab leaf as; DLimonene; (1) Thunbergol (2) and Cis-2-Methyl-7-octadecene (3) with significant antioxidant potential. The chemical components were identified for the first times.